Age and sex disparities in hypertension control: The multi-ethnic study of atherosclerosis (MESA) - Nkiru Osude; Ramon Durazo-Arvizu; Talar Markossian; Kiang Liu; Erin D. Michos; Michael Rakotz; Gregory Wozniak; Brent Egan; Holly Kramer (Elsevier, 2021)
Objective: Determine sex differences in hypertension control by age group in a diverse cohort of adults age 45-84 years at baseline followed for an average of 12 years. Methods: The Multi-Ethnic Study of Atherosclerosis enrolled 3213 men and 3601 women from six communities in the U.S. during years 2000-2002 with follow-up exams completed approximately every two years. At each exam, resting blood pressure (BP) was measured in triplicate, and the last two values were averaged. Hypertension was defined as a BP ≥ 140/90 mmHg and/or use of antihypertensive medications. Hypertension control was defined as a BP < 140/90 mmHg and in separate analyses as < 130/90 mmHg. Generalized linear mixed effects models with a binomial function were used to calculate the odds of hypertension control by age group (45-64,75-74, 75+) at a given exam and by sex, while accounting for the intra-individual correlation, and adjustment for demographics, co-morbidities, smoking, alcohol use, education and site among participants with hypertension at any of the first five exams. Results: At baseline, mean age was 64.1 (9.1 [SD]) years, 48.0% were men, and race/ethnicity was Non-Hispanic white in 34.1%, 10.1% Chinese, 35.1% Non-Hispanic Black and 20.7% Hispanic. Average SBP was lower while average DBP was higher among men vs. women at each exam. Adjusted odds ratios of hypertension control defined as BP < 140/90 mmHg among men vs. women was 0.89 (95% CI 0.67, 1.19) for age 45-64 years, 1.37 (95% CI 1.04, 1.81) for age 65-74 years and 2.08 (95% CI 1.43, 3.02) for age 75+ years. When defined as < 130/80 mmHg, adjusted odds of hypertension control among men vs. women was 0.60 (OR 0.60; 95% CI 0.46, 0.79) at age 45-64 years, 1.01 (OR 1.01; 95% CI 0.77, 1.31) at age 65-74 years and 1.71 (95% CI 1.19, 2.45) at age 75+ years. Conclusion: Sex disparities in hypertension control increase with advancing age and are greatest among adults age 75+ years.